BO’LAJAK GEOGRAFIYA FANI O’QITUVCHILARINING PEDAGOGIK FAOLIYATINI RIVOJLANTIRISH IMKONIYATLARI VA INNOVATSION YONDASHUVLAR - Bahromova Muhayyo Imomqul qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract.  The  article  provides  detailed  information  on  opportunities  and innovative approaches for developing the pedagogical activities of future geography teachers.  It  discusses  effective  teaching  mechanisms  through  modern  education, information and communication technologies, and didactic tools, as well as ways to improve quality in higher education institutions. The importance of innovation and novelty in education, their differences, and their impact on the education system are analyzed.  The  article  emphasizes  the  necessity  of  using  innovative  approaches  in pedagogical  activity  to  enhance  the  quality  of  education  and  prepare  learners  as specialists capable of meeting the demands of modern society. The  article  also  analyzes  various  approaches  to  implementing  pedagogical innovations  in  higher  education  institutions,  including  individual,  multi-subjective, humanistic,  and  individual-creative  approaches.  It  discusses  the  opportunities  for educators to adopt and apply new pedagogical technologies, including the integration of innovative teaching methods and technologies into the classroom process.